E-Commerce in Agro-food industry in Zimbabwe: myth or reality - Mupemhi, Shepherd; Mupemhi, Ronicah; Duve, Richard (Cosmic Journals, 2016)
Electronic commerce has become a valuable model for the growth of business in every sector of the economy. This paper examines the level of e-commerce adoption in agro-food firms in Zimbabwe. A cross-sectional design using a survey method is used. The results show that e-commerce growth in agro-food firms in Zimbabwe is still at the embryonic stage. The implications to industry and the whole economy are discussed.